Continuous Erector Spinae Plane Block for Rescue Analgesia in Thoracotomy After Epidural Failure: A Case Report. Issue 10 (15th May 2017) - Forero, Mauricio; Rajarathinam, Manikandan; Adhikary, Sanjib; Chin, Ki Jinn
Abstract : The ultrasound-guided erector spinae plane (ESP) block is a newly described technique for providing thoracic analgesia. It is simple to perform and relatively noninvasive compared with thoracic epidural analgesia. In addition, the anatomy lends itself well to catheter insertion for continuous blockade. In this report, we describe the use of the ESP block as a rescue analgesic technique for postthoracotomy analgesia in a patient with failed thoracic epidural analgesia.